Electrocardiographic Predictors of Electroanatomic Scar Size in Arrhythmogenic Right Ventricular Cardiomyopathy: Implications for Arrhythmic Risk Stratification. (9th September 2013) - ZORZI, ALESSANDRO; MIGLIORE, FEDERICO; ELMAGHAWRY, MOHAMED; SILVANO, MARIA; MARRA, MARTINA PERAZZOLO; NIERO, ALICE; NGUYEN, KIM; RIGATO, ILARIA; BAUCE, BARBARA; BASSO, CRISTINA; THIENE, GAETANO; ILICETO, SABINO; et al.
ECG Predictors of Electroanatomic Scar in ARVC Introduction The extent of right ventricular (RV) electroanatomic scar (EAS) detected by endocardial voltage mapping (EVM) is a powerful invasive predictor of arrhythmic outcome in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC). Electrocardiogram (ECG) and signal‐averaged ECG are noninvasive tools of established clinical value for the diagnosis of electrical abnormalities in ARVC. This study was designed to assess the role of ECG and SAECG abnormalities for noninvasive estimation of the extent and regional distribution of RV‐EAS and prediction of scar‐related arrhythmic risk. Methods and Results The study population included 49 consecutive patients (38 males, median age 35 years) with a definite diagnosis of ARVC and an abnormal EVM by CARTO system. At univariate analysis, the presence of epsilon waves, the degree of RV dilation, the severity of RV dysfunction, and the extent of negative T waves correlated with RV‐EAS% area. Normal T‐waves were associated with a median RV‐EAS% area of 4.9% (4.5–6.4), negative T waves in V1–V3 of 22.0% (8.5–30.6), negative T waves in V1–V3 extending to lateral precordial leads (V4–V6) of 26.8% (11.5–35.2), and negative T waves in both precordial (V2–V6) and inferior leads of 30.2% (24.8–33.0) (P < 0.001). At multivariate analysis, the extent of negative T waves remained the only independent predictor of RV‐EAS% area (B = 4.4, 95%CI 1.3–7.4, P = 0.006) and correlated with the arrhythmic event‐rate during follow‐up (P = 0.03). Conclusions In patients with ARVC, the extent of negative T‐waves across 12‐lead ECG allows noninvasive estimation of the amount of RV‐EAS and prediction of EAS‐related arrhythmic risk.